The research on ethnic tolerance in polyethnic youth environment - Zh V Puzanova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2010)
The article presents a synopsis of the results of empirical sociological research on ethnic tolerance conducted in PFUR from 2008 to 2010. Special attention is given to the estimation of ethnic tolerance level at polyethnic youth environment and identification of the factors that influence the tolerance.